Optimization of D-limonene and phenolic compounds extraction from local Indonesian orange peel using ultrasound-assisted extraction - Wa Ode Cakra Nirwana; Dewi, Luthfi Kurnia; Larasati, Cindy; Anggraini, Oktavia; Hapsari, Safrina (Jurnal Rekayasa Proses, 2025)
Malang Regency is one of the orange plantation centers in East Java, Indonesia, and has been named Indonesia’s orange agrotourism area. Orange peel waste in Indonesia has not been utilized, even though orange peel contains valuable compounds, such as D-limonene and polyphenols. To date, studies on the extraction of D-limonene and total phenolic compounds (TPC) from Baby Java Pacitan orange (Citrus sinensis L.) and Keprok Batu 55 oranges (Citrus reticulata Blanco) has not been investigated. In this work, several factors affecting the extraction of D-limonene and total phenolic compounds from local Indonesian orange peels with ultrasonic assistance were investigated and optimized. The results showed that drying using a vacuum oven and agitation significantly increased the yield of D-limonene and TPC. The optimum condition for extracting D-limonene was a solid-solvent ratio (SSR) of 1:10 with an ethanol concentration of 96% for 40 minutes. Meanwhile, the optimum condition for extracting polyphenol compounds was a solid-solvent ratio of 1:10 with an ethanol concentration of 96% for 80 minutes. Under optimum conditions, Baby Java Pacitan orange peel produced D-limonene of 130.5 mg/g dry biomass, which was 2.8 times higher than Keprok Batu 55 orange peel. Meanwhile, the TPC for Baby Java Pacitan orange peel and Keprok Batu 55 orange peel were 46.1 mgGAE/g dry biomass and 43.9 mgGAE/g dry biomass, respectively.